Entre a Sociedade Civil Organizada e o Estado: embates, tensões e alianças no processo de construção do campo adotivo nacional - Oliveira Filho, Antônio Diogo Cals de (2013)
The following paper was written seeking further compreension of the brazilian adoption scene’s construction process. This social space has been built with the help of several social actors from the organized civil society and the State wich have been clashing their interests for the last 30 years, seeking oficial field nomination process as well as growing their symbolic laws and guidelines that can regulate adoption actions in the country. This text was made after mine living in the adoptive field, based on the experience with the Grupo de Apoio à Adoção de Fortaleza – GAAD Laços de Amor, and on the participation of Encontros Nacionais de Adoção, - ENAPAS, at São Paulo, 2009, Curitiba, 2011 and Brasília, 2012. After the participation on the GAAD, and the compilation of the national adoption movement main orator’s speeches, I noticed the formation of a complex of social actors that are gathering togheter around a common theme, the adoption in the country; in the last 30 years, they have been building a complex network aiming to control the children delivery process on the adoptioin and the profile changes of the adopters. Of these groups, the GAADs and the Judiciary have been highlighted, with the personal interest of their members, groups, classes and fractions of classes, and the new imaginary children and teenagers socials, they have been changing and creating new national laws like the Plano Nacional de Convivência Familiar e Comunitária, 2006, O Cadastro Nacional de Adoção, CNA, 2008 and the Nova Lei Nacional de Adoção, 2009. This process is heading to a union between the State and the organized civil society, looking after teaching the several adoption pratices, mostly to whom are outside of the oficial nomination sphere, such as biological parents whom give their childs to adoption and adopters, creating dispute between classes and groups wich stands in a social grey area that uses the complex laws as a strategy to get their interests performed.